PENGARUH PEMBERIAN HEALTH EDUCATION (HE) TENTANG PENYAKIT MENULAR SEKSUAL TERHADAP Â TINGKAT PENGETAHUAN REMAJA TENTANG PENYAKIT Â MENULAR SEKSUALÂ DI KELAS XI SMAN 1 BANGSAL MOJOKERTO - Triwibowo, Heri; Frilasari, Heni (JURNAL KEPERAWATAN SEHAT, 2015)
Sexually transmitted diseases was still a matter of health, social, or economic in various countries. Increased incidence of sexually transmitted disease and its spread throughout the world can not be estimated precisely. Some countries mentioned that the implementation of an intensive counseling program that will reduce the incidence of sexually transmitted diseases, or at least relatively fixed insidensnya. The purpose of the study was to determine th eeffect of health education about sexually transmitted diseases on the level of knowledge of adolescents about sexuall ytransmitted diseasesin SMAN 1 Bangsal Mojokerto. This research design using pre experimental research with one group pretest posttest design disign. populationwasallstudents of class XI in SMAN 1 Bangsal District. Mojokerto which totaled 343 students to 189 students got taken by cluster random sampling. Independent variable in this study is the provision of Health Education (HE) and the dependent variable in this study is the level of knowledge about sexually transmitted diseases. Data taken using questionnaires. After the data collected statistical test followed by Wilcoxon signed rank test using SPSS version 17. Study results indicate levels of knowledge adolescents XI of SMAN 1 Bangsal Mojokerto before given health education (HE) withless criteria as much as 187 (98%), the level of knowledge classteenagers XI of SMAN 1 Bangsal Mojokerto after respondent swere given health education (HE) sufficient criteriato 96 (50.8%), based on the value obtained wilcoxon teststatistic Z = -10.362 where p = 0.000 and p <0.05 then Ho isrejected. Meansitcan becon cluded thatthereis the effect of health education about sexually transmitted diseases on the level of knowledge of adole scents about sexually transmitteddiseasesinclass XI of SMAN 1 Bangsal Mojokerto. The next researchers studied the influence of the media are expected to achievement of health education (HE) on sex education.Key words: Health Education (HE), knowledge, sexually transmitted diseases, teen